2006
DOI: 10.1038/nrn2024
|View full text |Cite
|
Sign up to set email alerts
|

The mirror neuron system and the consequences of its dysfunction

Abstract: The discovery of premotor and parietal cells known as mirror neurons in the macaque brain that fire not only when the animal is in action, but also when it observes others carrying out the same actions provides a plausible neurophysiological mechanism for a variety of important social behaviours, from imitation to empathy. Recent data also show that dysfunction of the mirror neuron system in humans might be a core deficit in autism, a socially isolating condition. Here, we review the neurophysiology of the mir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
791
2
23

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,163 publications
(856 citation statements)
references
References 108 publications
40
791
2
23
Order By: Relevance
“…Human mirror neuron research has indicated that perceiving an action activates similar cortical networks as executing the same action (Gallese, Fadiga, Fogassi, & Rizzolatti, 1996; for a review see Iacoboni & Dapretto, 2006). This corresponds to the notion that perception and action share common representational codes (Hommel, Müsseler, Aschersleben, & Prinz, 2001;Prinz, 1990Prinz, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Human mirror neuron research has indicated that perceiving an action activates similar cortical networks as executing the same action (Gallese, Fadiga, Fogassi, & Rizzolatti, 1996; for a review see Iacoboni & Dapretto, 2006). This corresponds to the notion that perception and action share common representational codes (Hommel, Müsseler, Aschersleben, & Prinz, 2001;Prinz, 1990Prinz, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Both object words and verbs evoked more activation in IPL than subject words and the checkerboard did, indicating that the mirror neuron system in the bilateral parietal lobe may reflect action representation in the brain (Iacoboni & Dapretto, 2006). Object words induced stronger activation in the right precentral gyrus/inferior frontal gyrus (BA44) than subject words and the checkerboard did, indicating that the mirror neuron system in the right ventral frontal lobe is more sensitive to the pre‐presented object word.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroimaging studies have provided abundant and strong evidence for the role of the mirror neuron system (MNS) in action observation and imitation (Iacoboni & Dapretto, 2006; Iacoboni et al., 1999; Molenberghs, Brander, Mattingley, & Cunnington, 2010; Molnar‐Szakacs, Kaplan, Greenfield, & Iacoboni, 2006; Montgomery & Haxby, 2008; Rizzolatti, Cattaneo, Fabbri‐Destro, & Rozzi, 2014; Rizzolatti & Craighero, 2004; Rizzolatti, Fogassi, & Gallese, 2001; Rizzolatti & Sinigaglia, 2010). These data clearly show that a frontoparietal mirror neuron system underlying imitation coincides with that which is active during action observation.…”
Section: Introductionmentioning
confidence: 99%
“…As explained in an earlier section, this is because infants are capable of understanding very basic similarities about self and other, but are not capable of running a highly cognitive process like a simulation. On the other hand, ST might be able to overcome the problem of infant simulation by appealing to mirror neuron or some other neurological research (Brothers 1989, p. 13;Iacoboni 2009;Iacoboni and Dapretto 2006;Chakrabarti and Baron-Cohen 2006;Preston and De Waal 2002;Gallese 2003). Mirror neurons are special neurons that people (as well as several other animals) possess that regularly fire both when I perform an action and when I observe others performing a similar action.…”
Section: The Relation Between Simulations and Narrativesmentioning
confidence: 99%